2007
DOI: 10.1371/journal.pgen.0030102
|View full text |Cite|
|
Sign up to set email alerts
|

COUP-TFII Mediates Progesterone Regulation of Uterine Implantation by Controlling ER Activity

Abstract: Progesterone and estrogen are critical regulators of uterine receptivity. To facilitate uterine remodeling for embryo attachment, estrogen activity in the uterine epithelia is attenuated by progesterone; however, the molecular mechanism by which this occurs is poorly defined. COUP-TFII (chicken ovalbumin upstream promoter transcription factor II; also known as NR2F2), a member of the nuclear receptor superfamily, is highly expressed in the uterine stroma and its expression is regulated by the progesterone–Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
196
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(206 citation statements)
references
References 67 publications
9
196
0
1
Order By: Relevance
“…3 A and B). The expressions of Pgr-regulated genes Indian hedgehog (Ihh) (18), amphiregulin (Areg) (19), homobox A10 (Hoxa10) (20), nuclear receptor subfamily 2, group F, member 2 (Nr2f2) (18), and heart and neural crest derivatives expressed transcript 2 (Hand2) (21) were significantly decreased, and E2 target genes mucin 1 (Muc1), Muc4, lactotransferrin (Ltf), and complement component 3 (C3) (21,22) were significantly increased in OEx mice compared with control mice (Fig. 3 C and D).…”
Section: N1icd Overexpression Mice Are Completely Infertile Because Omentioning
confidence: 99%
See 1 more Smart Citation
“…3 A and B). The expressions of Pgr-regulated genes Indian hedgehog (Ihh) (18), amphiregulin (Areg) (19), homobox A10 (Hoxa10) (20), nuclear receptor subfamily 2, group F, member 2 (Nr2f2) (18), and heart and neural crest derivatives expressed transcript 2 (Hand2) (21) were significantly decreased, and E2 target genes mucin 1 (Muc1), Muc4, lactotransferrin (Ltf), and complement component 3 (C3) (21,22) were significantly increased in OEx mice compared with control mice (Fig. 3 C and D).…”
Section: N1icd Overexpression Mice Are Completely Infertile Because Omentioning
confidence: 99%
“…S4D). Exogenous hormones (P4 and E2) were used to prime the uterus of ovariectomized mice to mimic the receptivity of the uterus at 3.5 dpc, independent of the effects of ovarian factors (22). This treatment was capable of inducing a decidualization response after an artificial stimulation.…”
Section: N1icd Overexpression Mice Are Completely Infertile Because Omentioning
confidence: 99%
“…One of the major attributes of P 4 action is to regulate the epithelial oestrogen action tightly. Importantly, P 4 by acting via stromal PGR attenuates the oestrogeninduced epithelial gene expression (Kurihara et al 2007). Thus, P 4 elicits stromal cell decidualization via Ihh-Nr2f2-Bmp2 signalling.…”
Section: Discussionmentioning
confidence: 96%
“…The endometrium differentiates into an altered state when the blastocysts are capable of mediating effective two-way communication to initiate the process of implantation (Dey et al 2004). The molecular mechanism underlying this interaction is poorly defined; however, a novel signalling pathway involving Ihh-Nr2f2-Bmp2 has been implicated in the process (Kurihara et al 2007). The Pgr-knockout mouse model demonstrated that Figure 9 Working model of PN in mediating anti-decidualizing effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation